Mitochondrial pathways of copper neurotoxicity: focus on mitochondrial dynamics and mitophagy - Aschner, Michael; Skalny, Anatoly V.; Lu, Rongzhu; Martins, Airton C.; Tizabi, Yousef; Nekhoroshev, Sergey V.; Santamaria, Abel; Sinitskiy, Anton I.; Tinkov, Alexey A. (Frontiers in Molecular Neuroscience, 2024)
Copper (Cu) is essential for brain development and function, yet its overload induces neuronal damage and contributes to neurodegeneration and other neurological disorders. Multiple studies demonstrated that Cu neurotoxicity is associated with mitochondrial dysfunction, routinely assessed by reduction of mitochondrial membrane potential. Nonetheless, the role of alterations of mitochondrial dynamics in brain mitochondrial dysfunction induced by Cu exposure is still debatable. Therefore, the objective of the present narrative review was to discuss the role of mitochondrial dysfunction in Cu-induced neurotoxicity with special emphasis on its influence on brain mitochondrial fusion and fission, as well as mitochondrial clearance by mitophagy. Existing data demonstrate that, in addition to mitochondrial electron transport chain inhibition, membrane damage, and mitochondrial reactive oxygen species (ROS) overproduction, Cu overexposure inhibits mitochondrial fusion by down-regulation of Opa1, Mfn1, and Mfn2 expression, while promoting mitochondrial fission through up-regulation of Drp1. It has been also demonstrated that Cu exposure induces PINK1/Parkin-dependent mitophagy in brain cells, that is considered a compensatory response to Cu-induced mitochondrial dysfunction. However, long-term high-dose Cu exposure impairs mitophagy, resulting in accumulation of dysfunctional mitochondria. Cu-induced inhibition of mitochondrial biogenesis due to down-regulation of PGC-1α further aggravates mitochondrial dysfunction in brain. Studies from non-brain cells corroborate these findings, also offering additional evidence that dysregulation of mitochondrial dynamics and mitophagy may be involved in Cu-induced damage in brain. Finally, Cu exposure induces cuproptosis in brain cells due mitochondrial proteotoxic stress, that may also contribute to neuronal damage and pathogenesis of certain brain diseases. Based on these findings, it is assumed that development of mitoprotective agents, specifically targeting mechanisms of mitochondrial quality control, would be useful for prevention of neurotoxic effects of Cu overload.